Gramsci e il Sud come spazio di emancipazione - Fontana, Antonio (Italianistica Debreceniensis, 2018)
The paper will actively engage with the contradictions found in Gramsci in an attempt to tease out the elements of emancipation found in his thought, as well as a sub-culture of opposition against Western notions of rationality. Antonio Gramsci’s analysis of the Italian South and of the Southern Italian peasantry in relation to the formation of a radical politics of emancipation constitutes one of the most salient features of his critique of orthodox Marxism. I argue that for the Italian Marxist theorist, the liberation of the Italian peasantry is not only a project of social, economic and political emancipation. Rather, the peasantry’s emancipation is also seen as a project of cultural liberation, a liberation from the dominant strands of rationalist and positivist Enlightenment thought, which Gramsci saw as encapsulated in Crocean philosophy. For Gramsci, the task of the organic intellectuals is to create an ideational sphere in which the colonized South can potentially articulate and celebrate a culture that has historically been deemed backward and primitive. However, Gramsci’s analyses of the South also contain historicist encrustations, which create a dialectical tension in his theory of politico-cultural emancipation that has never really been solved. I argue that the positivist and progressionist encrustations of Gramsci’s program for the emancipation of the South is an instantiation of a wider, Western, 19th and 20th century intellectual tradition which conflates “progress” as such with emancipation, a tradition that goes beyond the Italian and European context, and that is even paralleled by the model for black emancipation in the American South put forth by a figure as seemingly divergent as, say, W.E. B. Du Bois in the The Souls of Black Folk (1903).